Edukasi Penggunan Pillbox Untuk Meningkatkan Kepatuhan Minum Obat Pasien Hipertensi - Kautsari, Farah Widya; Edhita Putri Daryanti (ABDIMAS Madani, 2023)
Hypertension is health problem around the world as a major risk factor for cardiovascular disease. Hypertension is also known as the Silent Killer that can be caused the sudden death of sufferers. One of the factors that causes hypertension patient have uncontrolled blood pressure and can cause various complications is nonadherence medication. The purpose of this community service is to increase compliance with taking medication for hypertension patients by using pill boxes. Community service activities were carried out on June 25th 2022 at Kradenan Piyungan Bantul. The method o this activity was giving education to the participant by using Ms. Power Point. The information provided was impact medication non-adherence and the use of pillboxes as a strategy to increase medication adherence. The results of this activity indicate that educational activities increase knowledge about medication adherence. Result pre-test and post-test increase from 40% to 92,22%. Keyword: Hypertension, Adherence, Pillbox